Do common genetic variants in FTO and MC4R influence weight change following dietary intervention. (22nd September 2015) - Sehmi, JS; Rai, BK; Chambers, JC; Kooner, JS
Abstract : Background: Central obesity, a major risk factor for diabetes and cardiovascular disease, is more common among Indian Asians than European whites. Although dietary intervention lowers weight, the reasons why diet is more effective in certain individuals than others are not known. Recent genomewide association studies show that common variants in FTO and MC4R are associated with obesity. Both loci are key regulators of appetite, energy intake and expenditure, but act through different pathways. We tested whether dietary intervention results in differential changes in weight, body mass index (BMI) and body fat among participants who carry one or more copies of the variant in FTO and MC4R, compared with wild type. Methods: We recruited 88 men and women aged 35–75 years with BMI greater than 26 kg/m 2 . Following an initial consultation with a dietician, each participant received personalised advice to reduce energy intake by ∼300 kcal per day. This was followed by weekly attendance at dietician-led group counselling sessions for 5 weeks and a final review at 3 months. All participants were given similar advice on physical activity. Body weight, height, and percentage body fat mass were recorded at recruitment and at each of the subsequent six visits. Genotyping for single nucleotide polymorphisms (SNP) rs12970134 near MC4R and rs8050136 in FTO was done by KASPar. Weight change was compared between genotype groups using linear regression. Results: Participants with the SNP rs12970134 near MC4R were of similar age, had similar BMI and fat mass percentages at baseline, compared with wild type. Following dietary intervention, participants with the MC4R variant had greater reduction in weight, BMI and body fat mass at 12 weeks, compared with wild type. In univariate analysis the MC4R variant was associated with changes in weight (p = 0.08), BMI (p = 0.08) and body fat mass (p = 0.04) between baseline and 12 weeks. In multivariate analysis there was a significant association between the MC4R variant and changes in weight (p = 0.03), BMI (p = 0.02) and body fat mass (p = 0.009) following adjustment for age, sex, diabetes and physical activity. Participants with SNP rs8050136 in FTO were of similar age, had similar baseline BMI but had a greater proportion body fat mass compared with wild type. Genetic variation in FTO was not associated with changes in weight, BMI or body fat (p>0.05) following dietary intervention (see tables 1 and 2). Conclusions: The MC4R, but not FTO, genotype is an independent predictor of body weight, BMI and fat mass reduction following dietary intervention. Results of this study lend support to the approach of personalised dietary intervention based upon the MC4R genotype.